“Outcomes of Iontophoresis Cross-Linking in Asymmetric Keratoconus: A Retrospective Analysis of High Visual Acuity Eyes Under 25 Years Old” - Ferraro V; Santoru F; Barone G; Rosetta P (Clinical Ophthalmology, 2024)
Vanessa Ferraro,1,2 Francesco Santoru,1,2 Gianmaria Barone,1,2 Pietro Rosetta3 1Department of Ophthalmology, IRCCS Humanitas Research Hospital, Milan, Italy; 2Department of Biomedical Sciences, Humanitas University, Milan, Italy; 3Department of Ophthalmology, Humanitas San Pio X, Milano, Milan, ItalyCorrespondence: Vanessa Ferraro, Department of Biomedical Sciences, Humanitas University, Via Rita Levi Montalcini 4, Pieve Emanuele, Milan, 20090, Italy, Tel +393406701716, Email vanessa.ferraro@st.hunimed.euPurpose: To assess the long-term outcomes of transepithelial iontophoresis cross-linking (I-CXL) for early keratoconus with high visual acuity under the age of 25.Methods: This retrospective study was conducted at the Department of Ophthalmology, Humanitas San Pio X, Milan, Italy, on data collected between 2015 and 2020. Patients diagnosed with early keratoconus and under the age of 25 who underwent to I-CXL were retrospectively reviewed and included in the study if they fulfilled the following criteria: high visual acuity (LogMAR ≤ 0.2) before I-CXL and the fact that the fellow, most advanced eye, had been treated with epithelium off CXL (S-CXL). Corrected distance visual acuity (CDVA), spherical equivalent refraction, thinnest corneal thickness, corneal topography and tomography were assessed at baseline and at least 24 months of follow-up, using Pentacam. Statistical analysis was performed with STATA SE version 17.Results: Twenty patients with a mean age of 18.5 ± 3.75 months were included. The median follow-up time was 24 months. The statistical analysis showed no significant change over time in CDVA, maximum keratometry and A, B, C values of the Belin Progression Display. Mean baseline CDVA was 0.03 ± 0.07 logMAR, whereas at 24-month was 0.01 ± 0.04. Mean spherical equivalent was − 1.29 ± 1.38D at baseline and − 1.05 ± 1.51D after 24 months. Preoperative maximum keratometry was 48.35 ± 4.95 D and 48.56 ± 4.96 D after the 2 years of follow-up. Mean baseline A value was 7.13 ± 1.66 mm and 24-month postoperative was 7.43 ± 0.48 mm. Average B value was 5.87 ± 0.55 mm prior to surgery, while it was 5.83 ± 0.60 mm after the last follow-up. Mean baseline and 24-month thinnest point were 498.9 ± 34.29 μm and 500.10 ± 33.45 μm respectively. None of the patients showed a progression of keratoconus.Conclusion: I-CXL may be considered as a beneficial treatment option for young patients with less advanced keratoconus, although further consensus on patient selection criteria is needed.Keywords: keratoconus, ectasia progression, cross-linking treatment, iontophoresis